2001
DOI: 10.1007/s00417-001-0397-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of autologous platelet concentrate and serum on retinal wound healing in an animal model

Abstract: We have demonstrated a significantly greater proliferative cellular response in the healing of retinal wounds with the use of platelet concentrate than in control wounds. We consider that this model may be used in further studies on the effects of other agents on retinal wound healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
0
8
0
2
Order By: Relevance
“… 5 , 16 , 17 , 38 As in some cases described by other authors, 14 – 17 two of our patients presented with a break in the tissue overlying the ODP, and the vitreous remained attached in both cases, visualized before and during surgery. We believe that the use of APC with its mitogenic and chemotactic properties, 39 associated with posterior hyaloid peeling to eliminate vitreomacular traction, favors the proliferative cellular response and closure of the suspected communication between the vitreous and the retina and, secondarily, promotes reabsorption of intra- and subretinal fluid.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 16 , 17 , 38 As in some cases described by other authors, 14 – 17 two of our patients presented with a break in the tissue overlying the ODP, and the vitreous remained attached in both cases, visualized before and during surgery. We believe that the use of APC with its mitogenic and chemotactic properties, 39 associated with posterior hyaloid peeling to eliminate vitreomacular traction, favors the proliferative cellular response and closure of the suspected communication between the vitreous and the retina and, secondarily, promotes reabsorption of intra- and subretinal fluid.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, autologous platelet releasate 14 as well as recombinant platelet-derived growth factors 15 may enhance healing of chronic lower extremity diabetic ulcers. Moreover, regeneration of cutaneous wounds, 16 retina, 17 and peri-implant bone 18 by platelets has been reported. However, treatment of surgical lesions with plateletrich plasma has also generated controversial results in clinical trials.…”
mentioning
confidence: 99%
“…The combination of adipose tissue and PRP was found by some researchers to enhance graft adherence (Cullinane et al. 2002 ). In a respective cohort study estimating the effectiveness of platelet foot ulcers, the researchers found that the relative risk for a wound to heal after treatment was 95% when compared to the standard of care (Margolis et al.…”
Section: Discussionmentioning
confidence: 99%